2000
DOI: 10.1007/pl00001903
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Treatment and Satisfaction with Dental Appearance among Young Finnish Adults with and without a History of Orthodontic Treatment

Abstract: The aim of this investigation was to evaluate orthodontic treatment need and patient satisfaction among young adults living in a city where free-of-charge orthodontic treatment was provided. A total of 281 18- to 19-year-old subjects randomly selected from the population register of the city of Vantaa took part in the study. The drop-out rate was 30%. Treatment need was clinically assessed according to the Index of Orthodontic Treatment Need (IOTN), consisting of a Dental Health Component (DHC) and an Aestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
25
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 26 publications
15
25
2
Order By: Relevance
“…In this study, the need for treatment was observed in 21.4% of all the subjects. This percentage is higher than in Finnish studies (15% of the subjects required treatment), comparable to British (21%) and French (21%) findings and lower than results obtained by Italian researchers (27.3%) [16][17][18][19].…”
Section: Discussionsupporting
confidence: 51%
“…In this study, the need for treatment was observed in 21.4% of all the subjects. This percentage is higher than in Finnish studies (15% of the subjects required treatment), comparable to British (21%) and French (21%) findings and lower than results obtained by Italian researchers (27.3%) [16][17][18][19].…”
Section: Discussionsupporting
confidence: 51%
“…The same level of satisfaction (74%) that was found among the present untreated respondents has also been reported among 15-to 16-year-olds by Pietilä and Pietilä 10 and Sheats et al 20 In older age groups, satisfaction has been higher, between 89% and 94%. 7,21,22 The low satisfaction among the treated subjects in our study may be related to the fact that the Finnish publicly funded orthodontic care gives priority to functional aspects instead of esthetics. 12 Compared with the rather low satisfaction level, only a few of the respondents expressed a need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Indices designed for evaluation of orthodontic treatment need have also been applied to assess the outcome, including the residual treatment need among orthodontic patients [12][13][14][15][16][17]. The Occlusal Morphology and Function Index (OMFI) was developed to clinically evaluate the outcome of orthodontic care at the population level.…”
Section: Introductionmentioning
confidence: 99%